Expanded Makuuchi's criteria using estimated indocyanine green clearance rate of future liver remnant as a safety limit for maximum extent of liver resection. Issue 8 (August 2019) - Kobayashi, Yuta; Kiya, Yoshitaka; Sugawara, Toshitaka; Nishioka, Yujiro; Hashimoto, Masaji; Shindoh, Junichi
Abstract: Background: Recent advances in liver surgery have dramatically improved the safety of hepatectomy for hepatocellular carcinoma (HCC). The aim of this study was to compare outcomes for patients fulfilling an extended criteria vs. those fulfilling the conventional criteria based on the bilirubin and indocyanine green (ICG) clearance (Makuuchi's criteria). Methods: The short term outcomes of patients undergoing hepatectomy for HCC and who fulfilled the expanded criteria (ICG clearance of future remnant liver [ICG-Krem] ≥ 0.05 estimated using 3-D volumetry) were retrospectively reviewed and were compared between those fulfilling the conventional criteria. Postoperative hepatic insufficiency (PHI) was defined as peak total bilirubin >7 mg/dL. Results: A total of 323 patients undergoing resection of whom 269 (83%) met conventional criteria (In-M) and 54 (17%) extended criteria (Ex-M). The overall morbidity rates were not significantly different. The incidence of PHI was 0.37% in In-M and 3.7% in Ex-M (P = 0.074), with no liver-related deaths. When the ICG-Krem ≥ 0.05 criterion was included, major hepatectomy was performed in 24 patients (41%) in Ex-M with no significant increase in major morbidity (13%), PHI(3.3%), or liver-related death (0%) compared with minor hepatectomy (n = 30) in Ex-M(10%, 4% and 0%, respectively). Conclusions: Objective criteria using ICG clearance rate and 3-D volumetry may offer opportunities for safe surgical resection in selected patients exceeding the conventional criteria.